PROBLEMS IN THE ERA OF GLOBALIZATION AND INNOVATIVE SOLUTIONS TO THEM - Yuldasheva Dilnoza Bekmurodovna; Egamkulov Davlatbek Bakhodirovich (Galaxy International Interdisciplinary Research Journal, 2023)
This article is about the process of accelerated globalization today, and we will conduct an analysis of the attitudes that are occurring in practice. In the course of the analysis, the treats will be studied from the subjective and objective side and will consist in making scientifically based suggestions and feedback.